Bile duct injuries due to cholecystectomy, preventive measures and management possibilities - Jonathan Luis Gonzabay Muñoz; Mónica Gabriela Chachalo Sandoval; Santiago Xavier Peñarreta Quezada (Medisur)
Biliary stone disease is a common entity and one of the main hospital emergencies. Cholecystectomy is the treatment of choice and its performance can cause injury to the bile ducts. The objective of this work was to describe bile duct injuries due to cholecystectomy, preventive measures and management possibilities for this condition. A search of indexed sources was carried out in: Pubmed, Embase and Scielo. The occurrence of bile duct injuries due to cholecystectomy, preventive measures and management possibilities were discussed to highlight the importance of prevention and treatment to reduce the surgical risks associated with the treatment of this entity. Among the main injuries secondary to cholecystectomy, circumferential injury to major bile ducts and lateral injury to the bile duct were noted. These lesions can be prevented by the tri-structure method and intraoperative cholangiography, they can be addressed with surgical treatment, endoscopy and interventional radiology.